Peningkatan Pelayanan PMB Berbasis Android di Politeknik Harapan Bersama Tegal - Arfan Haqiqi Sulasmoro; Arif Rakhman; Nurohim (Journal of Innovation Information Technology and Application (JINITA), 2020)
Currently the development of information and communication technology has been approved by the aspects of human life, undeniable in the field of education including the development of mobile technology that presents SmatPhone in various functions that are not only as a means of communication, but also use today's information sources. This creates greater public demand for information on education and encourages Educational Institutions including the Harapan Bersama Tegal Polytechnic to use it as an information media and to register prospective new students based on Android. This study takes the theme "Improving Android-Based PMB Services at the Polytechnic of Harapan Bersama Tegal" with the aim of assisting new students in registering using the SmatPhone device and to assist the Polytechnic of Hope together in processing registration data. This application is a development of an application that was previously still using the Web, then developed into an Android-Based PMB Application by developing using the MIT Ai2 programming that can run on the Android operating system